Growth of {100}-faceted NaFeTiO4 crystals with a tunable aspect ratio from a NaCl–Na2SO4 binary flux. Issue 7 (3rd January 2018) - Sudare, Tomohito; Kawaura, Daiki; Yubuta, Kunio; Hayashi, Fumitaka; Teshima, Katsuya
Abstract : The controlled growth of NaFeTiO4 crystals with needle and planar bar shapes from a NaCl–Na2 SO4 binary flux with different compositions. Abstract : The controlled growth of needle-shaped and planar bar-shaped NaFeTiO4 crystals, a CaFe2 O4 -type structure, was carried out by a flux method using a NaCl–Na2 SO4 binary flux. NaCl fluxes have been empirically investigated for growing unique anisotropic crystal shapes. However, strategies for controlling the crystal morphology based on NaCl fluxes have not been established. In this study, Na2 SO4 was added to a NaCl flux to supply O 2− ions, which is essential for the dissolving ability of a metal oxide into ions, and the growth manner was systematically investigated as a function of flux composition. As a result, needle-shaped crystals were obtained from the pure NaCl flux with exposed {100} facets. Meanwhile, with the binary flux, the morphology of the crystals changed from a needle shape to a planar bar shape depending on the Na2 SO4 content, where the aspect ratio of the {100} facets was increased by about ten times. It was found out that the aspect ratio of the {100} planes of NaFeTiO4 crystals can be controlled kinetically by the cooperative effect of Na + ions and anionic species in the flux; Na + ions stabilize the {100} facets and a high O 2− /Cl − ratio increases the concentration of ions as a precursor for crystal growth to promote the growth in the <001> direction, resulting in planar bar-shaped crystals. We believe that the morphological control regime demonstrated here in the growth of NaFeTiO4 crystals in a NaCl–Na2 SO4 binary flux could be a useful idea in high temperature chemistry and for their desirable applications.